EFEKTIVITAS E-MODUL PEMBELAJARAN BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATIC) MATERI USAHA DAN ENERGI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA SISWA SMA - Yudha, Erwin Baruna Sandi; Prihatin, Jekti; Putra, Pramudya Dwi Aristya (IKIP PGRI Bojonegoro, 2024)
Critical thinking skills are a requirement that needs to be possessed in 21st-century learning. The development of e-modules based on the latest technology that can improve students' critical thinking skills is very important. The aim of this research is to determine the effectiveness of STEM-based learning e-modules on business and energy to improve critical thinking skills in high school students. Development research using 4D design. The purposive area sampling method resulted in 3 schools, namely SMAN 3 Jember, small and large group trials, distribution school trials, namely SMAN Mumbulsari and SMAN Jenggawah. The test subjects were class X high school students. The results of this research are that STEM-based learning e-modules are declared effective for improving critical thinking skills based on the N-gain value in small group trials of 0.68 in the medium category, large group trials of 0.72 in the high category, and school trials. spread of 0.65 in the medium category. The overall average N-gain value is categorized as moderate.